Proposta para o Serviço Educativo do Museu Municipal do Montijo : o livro infantil como estratégia de divulgação da Casa Mora - Almeida, Maria Julieta da Silva, 1993- (2017)
The study of heritage and of the heritage education are an important issue. This has effect on the psychic balance and progress of the human being. For instance, a book is a useful tool for the understanding, creation and evaluation of heritage safeguarding. The proposal of the book "A casa do Sr. Domingos" aims to transmit the youngest the history of Casa Mora, where is located the Municipal Museum of Montijo (Portugal) due to the lack of research and evaluation strategies for this place. For this proposal to be realized, it is necessary to study the relevance that the past testimonies have in the modern era, at various levels, from the meaning and concept of heritage, its connection with an identity and with an inheritance of individuals. It is also necessary to understand the contemporary behaviour of communities in relation to heritage. This knowledge can be used to an effective heritage education, and to have a clear idea of an interest that can change the lives of citizens. The proposal of these book, "A casa do Sr. Domingos", is oriented for a specific target audience: children from 7 to 12 years old. It is important to know the type of audience and to consider their cognitive development and their interests. Before that, it is also necessary to study the importance of children books in their lives and how they can contribute to their progress and to the opening of new awareness. Since Casa Mora has so little information available to municipalities and visitors in general, we believe that including a study of it in this essay will be very enriching, both for this work and for local history. Several visits were made to this place and, due to the lack of information, it was only possible to compile several testimonies and compare the architecture of the Montijo’s Municipal Museum (Casa Mora) building with other local buildings of the same period